PENGARUH BAURAN PEMASARAN DAN CITRA DESTINASI WISATA TERHADAP MINAT BERKUNJUNG KEMBALI MELALUI KEPUASAN WISATAWAN - Bella Bella; Umi Muawanah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study analyzes the Influence of Marketing Mix and Destination Image on Revisit Intention through Tourist Satisfaction which increases or decreases the value given to Revisit Intention. This study was conducted at the Sumber Sira tourist attraction located in Putukrejo Village, Gondanglegi District, Malang Regency. This research method, data was analyzed using path analysis with the help of the SPSS (Statistical Product and Solutions) 26.0 for Windows application program, with variables: Marketing Mix (X1), Tourist Destination Image (X2), Tourist Satisfaction (Y), and Revisit Intention (Z). The results of the study can be concluded as follows: The Marketing Mix variables (X1) and Tourist Destination Image (X2) influence visitors to feel Satisfaction visiting the Sumber Sira tourist attraction. The better the Marketing Mix and Tourist Destination Image (X2), the more visitors or tourists will be interested in revisiting the Sumber Sira tourist attraction. The better or increasing Tourist Satisfaction (Y) the more visitors or tourists will be interested in revisiting the Sumber Sira tourist attraction. Marketing Mix (X1) and Tourist Destination Image (X2) do not affect the Intention to Revisit (Z) through the mediation of Tourist Satisfaction (Y). Keywords: Marketing Mix, Tourist Destination Image, Intention to Revisit, Tourist Satisfaction.